Regional Income Redistribution and Risk Sharing : How Does Italy Compare in Europe? - Decressin, Jorg (IMF Working Papers; Working Paper ;, 1999)
This paper investigates income redistribution and risk sharing among Italy's regions and the implications for public policy. Using a richer data set than in previous works, this study allows for an assessment of public consumption's and investment's roles. The findings suggest that Italy's fiscal system provides interregional redistribution at 30-35 percent and risk sharing at 20-30 percent of GDP, mainly through public consumption. Compared with results in the literature for other European countries, there appears to be less redistribution and risk sharing in Italy through its welfare and tax systems because of their different structures.